Examining The Role of Competence, Job Satisfaction, And Work Discipline in Enhancing Employee Performance at Kuta Puri Bungalows Villa & Resort - Ni Kadek Duwik Susanti; Ni Made Satya Utami; Ary Wira Andika (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Human resources are a major factor in determining the success of an organization, so companies need to ensure that employee performance is optimized. Employee performance is influenced by several important factors, such as competence, job satisfaction, and work discipline. This study aims to analyze the influence of competence, job satisfaction, and work discipline on employee performance at Kuta Puri Bungalows Villa & Resort, which is motivated by the phenomenon of low competence standards, lack of employee satisfaction with career opportunities, and high absenteeism as an indicator of low work discipline. The population of this study was all 31 employees of Kuta Puri Bungalows Villa & Resort. The type of data used in this study is quantitative. The sample size was determined using saturated sampling technique with a sample size of 31 employees. The data analysis technique used is multiple linear regression which includes validity test, reliability test, classical assumption test, and t-test using SPSS program.